Using Web-Based GIS to Assess Students' Geospatial Knowledge of Hurricanes and Spatial Habits of Mind. Issue 2 (3rd March 2020) - Perugini, Sam; Bodzin, Alec M.
Abstract: Geospatial weather data is readily available to learners. However, the interpretation and understanding of this data requires the utilization of geospatial thinking skills. This study examined the impacts of a Web-based, collaborative inquiry Hurricane Irma GIS learning module on AP environmental science students' hurricane knowledge and spatial thinking skills. Study results showed significant improvement in knowledge about hurricanes, coastal impacts, and risks. A measure of spatial literacy found no changes in student self-assessment of spatial thinking skills resulting from the module. However, students did show significant improvement on hurricane knowledge questions associated with pattern recognition, spatial descriptions, and visualization.